Parents’ Knowledge Concerning School Phobia of their Children in Baghdad City, Iraq - Abdulmahdi A. Hasan (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Fear from school can also be described as any rejection by a child to join a school or to havedifficult time attending the school for a complete day by a child. Aims of the study: To describe parentsknowledge of their children with fear from school. Methodology: This study examined the analysis on thedata collected by the Ibn Alhythm primary School all through from the middle of October till the end ofJanuary 2011school year. The sample data took the form of surveys, questionnaires , and interviews by aresearcher with parents who have been analyzed to investigate the associations among variables related tofear from school behaviour. “Ibn Alhythm primary School District ‘s Special Education Department collecteddata during the 2010-2011 school year. In hopes of identifying a representative sample of the school-refusingstudents in the district, the Special Education Department sent participation requests to a random sample of40 of the 40 families described as having students who missed 18 or more days of the Ibn Alhythm primarySchool during the 2010-2011 school year. The information obtained did not include information from anystudents who were in Ibn Alhythm primary School through 1st grade or who missed fewer than 18 daysof school, the information has been analyzed through data analysis. The results: The results of the studyrevealed that the educational program had a positive impact on the knowledge of family members. Theresults of the study have demonstrated that there is a correlation between the mothers’ knowledge and theirdemographic characteristics (age of parents, educational level, occupation, residential area). In general,knowledge of parents related to fear was low. However, the parents applied preventive measure towardstheir children with fear .A quasi-experimental study was conducted in the Ibn Alhythm primary school fromthe middle of October till the end of January 2011.Recommendation: Keep the sample group large. Theauthor should get a fair representation of the population in doing so. Parents having a minimum level ofexperiences at school phobia, need a specific education program and training sessions. A specific educationprogram can be designed and described to parent’s who have a minimum level of knowledge to enhancetheir level of knowledge.”